Influential financial factors of employee engagement outcomes within SME business in Malaysia:A qualitative study. - Rashid, Safiah; Mohd Harif, Mohd Amy Azhar (Institute for Management and Business Research (IMBRe), Universiti Utara Malaysia, 2016)
A great deal of interest in employee engagement has been witnessed over the years. Even though previous researchers have established the relevance of employee engagement and their desired outcomes, an examination of the existing literature has revealed a gap. Against the backdrop of the importance of employee engagement within small-and-medium enterprises (SMEs), the purpose of this study was to qualitatively explore employee engagement outcomes at the organisational level, particularly the influential financial factors. Participants of this study shall include the top managers of SMEs in Malaysia. Eight financial factors namely profitability, productivity, revenue, business growth, account receivable, shrinkage, operating margin, and return-on-asset (ROA) were identified. This study will employ the snowball sampling technique and converging interviewing was suggested to be used to gather data to confirm the proposed conceptual framework. Finally, data will be analysed using content analysis.